Micro Frontend-Based Development: Concepts, Motivations, Implementation Principles, and an Experience Report - de Moraes, Fernando Rodrigues [UNESP]; Campos, Gabriel Nagassaki [UNESP]; de Almeida, Nathalia Rodrigues [UNESP]; Affonso, Frank José [UNESP] (My University, 2024)
Micro frontend is an architectural style that enables us to build large software systems by combining independent micro applications, which can boost different aspects related to the development (e.g., innovation, continuous software delivery), besides increasing the flexibility and scalability of the final application itself. Although there are numerous benefits related to this architectural style, some companies are still hesitant to adopt development based on micro frontends because of a lack of knowledge about concepts, development approaches, architectural models, and organizational aspects of the company. This paper presents the results of a Systematic Mapping Study (SMS) on micro frontends based on 16 studies. The results were synthesized in an important overview that addressed concepts, aspects related to development (i.e., development approaches, architectural models, and company organization), and micro frontend trade-offs based on three scenarios. Next, we present a case study on an inventory control application based on the knowledge of this SMS, analyzing the development under three approaches (i.e., Build-time, Frameworkless, and Framework-based). As result, we observed our paper has a good perspective to contribute efficiently to the micro frontend domain by providing an overview of this research area and an experience report for researchers and practitioners.
Keywords: Development Approaches; Micro Frontend Architecture; Web Development